The Influence of TikTok on Creativity in Media Production (Broadcasting Students Batch 2020 UBSI Margonda) - Anisti, Anisti; Mutiah, Tuty; Arieva, Dian (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The Tiktok application is now popular in Indonesia and globally as a social media platform that is growing rapidly. Tiktok provides a space for its users to express creativity through various video content. This research aims to evaluate the influence of Tiktok on the creativity of 2020 UBSI Margonda Broadcasting students. The approach used in this research is quantitative with a positivism paradigm, and the research design adopts a survey method. A total of 55 respondents were involved in this research, using random sampling techniques. The results of this research show that Tiktok social media has an effect on increasing student creativity.